Agricultural trade in Bhutan: Patterns, trends; and economic impact - Dem, Phub; Minot, Nicholas (International Food Policy Research Institute, 2010)
In spite of its remote and land-locked location, Bhutan has been relatively successful as an agricultural exporter. The value of agricultural exports has grown at an annual rate of almost 9% since 2000. Taking advantage of the cooler climate, Bhutan exports oranges, potatoes, vegetables, and apples to India and Bangladesh. At the same time, agricultural imports have been growing at 10% per year. Rice accounts for more than two-thirds of the value of agricultural imports, which is not surprising given that Bhutan depends on imports for about half of its consumption needs. Wheat, vegetables, fruits, and spices are also imported. A key question, however, is whether this trade in agricultural products is beneficial to Bhutan in general and to poor farmers and consumers in particular?